GAMIFIED ENGLISH INSTRUCTION MEDIATED BY KAHOOT! AT SENIOR HIGH SCHOOL: EVIDENCE FOR VOCABULARY GAINS - Mubarok, Doyfi Ibrahim Rizqi; Bilqis, Mutiara; Imamyartha, David (Sanata Dharma University Yogyakarta, 2025)
Learning vocabulary in a second or foreign language is necessary for effective communication. Because the process of memorizing vocabulary is boring and stressful for some high school students, they have poor vocabulary knowledge. This study is focused on investigating whether or not there is an effect of using Kahoot! on senior high school students' vocabulary achievement. This research was conducted in two classes, one of which was used as an experimental class, and the other was a control class. The duration of the treatment is two weeks, and the third week is to do a post-test. This research was carried out in one of the high schools in Jember City. To measure participants' achievement in vocabulary learning after the experiment, a vocabulary achievement test was developed by the researchers. To check the validity of the hypothesis, an independent sample t-test was run to determine the significant difference between the mean post-test score and the SPSS. The results of the study indicate that Kahoot is effective in improving the vocabulary learning of the experimental group.